2020
DOI: 10.1002/aoc.6082
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, DNA binding/cleavage, cytotoxic, apoptotic, and antibacterial activities of V(IV), Mo(VI), and Ru(II) complexes containing a bioactive ONS‐donor chelating agent

Abstract: New V(IV), Mo(VI), and Ru(II) complexes containing the ligand 2,4‐dihydroxyacetophenone‐S‐methyl dithiocarbazate (H2dhasm); [VO(dhasm)(bpy)] (1) (bpy = 2,2′‐bipyridine), [VO(dhasm)(phen)] (2) (phen = 1,10‐phenanthroline), [MoO2(dhasm)(imz)] (3) (imz = imidazole), [MoO2(dhasm)(DMSO)] (4) (DMSO = dimethylsulfoxide), and [Ru(CO)(PPh3)2(dhasm)] (5) have been synthesized. The ligand and its complexes were structurally characterized by elemental analyses, IR, 1H NMR, EPR, ultraviolet (UV)–visible spectroscopies, mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 98 publications
1
10
0
Order By: Relevance
“…Complex 1 , with a selectivity index (SI) of 5.24, is the most promising complex for HT-29 cells for effective antiproliferative activity. Nonetheless, under similar conditions all 1 – 5 show cytotoxic potential comparable to that of existing chemotherapeutic drugs such as cisplatin. , Moreover, the reported complexes showed promising cytotoxicity, in comparison to earlier reports of the related oxidovanadium complexes [KVO 2 (L 3 )] n and [KVO 2 (L 4 )­(H 2 O)] n (H 2 L 3 = (2,3-dihydroxy-benzylidene)-2-hydroxybenzohydrazide and H 2 L 4 = (2,3-dihydroxybenzylidene)­benzohydrazide] against the MCF-7 cell line (>200 μM), [VO­(sal-L-tryp)­(MeATSC)]·1.5C 2 H 5 OH (sal-L-tryp = N -salicylidene- l -tryptophanate, MeATSC = 9-anthraldehyde- N (4)-methylthiosemicarbazone) and [VO­(sal-L-tryp)­(N-ethhymethohcarbthio)]·H 2 O against the HT-29 cell line (>80 μM), and [V IV O­(1-(2-hydroxyphenyl)­diazenyl)­naphthane-2-ol)­(phen/bipy)] against the HeLa cell line (>44 μM) …”
Section: Resultssupporting
confidence: 44%
See 1 more Smart Citation
“…Complex 1 , with a selectivity index (SI) of 5.24, is the most promising complex for HT-29 cells for effective antiproliferative activity. Nonetheless, under similar conditions all 1 – 5 show cytotoxic potential comparable to that of existing chemotherapeutic drugs such as cisplatin. , Moreover, the reported complexes showed promising cytotoxicity, in comparison to earlier reports of the related oxidovanadium complexes [KVO 2 (L 3 )] n and [KVO 2 (L 4 )­(H 2 O)] n (H 2 L 3 = (2,3-dihydroxy-benzylidene)-2-hydroxybenzohydrazide and H 2 L 4 = (2,3-dihydroxybenzylidene)­benzohydrazide] against the MCF-7 cell line (>200 μM), [VO­(sal-L-tryp)­(MeATSC)]·1.5C 2 H 5 OH (sal-L-tryp = N -salicylidene- l -tryptophanate, MeATSC = 9-anthraldehyde- N (4)-methylthiosemicarbazone) and [VO­(sal-L-tryp)­(N-ethhymethohcarbthio)]·H 2 O against the HT-29 cell line (>80 μM), and [V IV O­(1-(2-hydroxyphenyl)­diazenyl)­naphthane-2-ol)­(phen/bipy)] against the HeLa cell line (>44 μM) …”
Section: Resultssupporting
confidence: 44%
“…Nonetheless, under similar conditions all 1−5 show cytotoxic potential comparable to that of existing chemotherapeutic drugs such as cisplatin. 116,117 Moreover, the reported complexes showed promising cytotoxicity, in comparison to earlier reports of the related oxidovanadium complexes [KVO 2 (L 3 )] n and [KVO 2 (L 4 )(H 2 O)] n (H 2 L 3 = (2,3-dihydroxy-benzylidene)-2-hydroxybenzohydrazide and H 2 L 4 = (2,3-dihydroxybenzylidene)benzohydrazide] against the MCF-7 cell line (>200 μM), 118 against the HeLa cell line (>44 μM). 35 As per DNA and BSA binding studies, 2 was expected to show greater toxicity, but 1 with an IC 50 value of 5.42 ± 0.15 μM was as the most cytotoxic compound, whereas 4, with an IC 50 value of 72.19 ± 0.12 μM, was the least cytotoxic among all.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The IC 50 values indicate that these complexes may act differently on different cell lines ascertaining them to be cell specific. Overall, the IC 50 values for Mo complexes (Table ) were found to be comparable or better than that of cisplatin, a commonly used chemotherapeutic drug. …”
Section: Results and Discussionmentioning
confidence: 85%
“…The test compounds were dissolved in a minimum amount of DMSO to assist solubility (should not exceed 0.1%-0.5% v/v to avoid its toxic effect on living cells. [94][95][96] The cell viability parentage against concentration through incubation periods The cytotoxic activity of each compound was determined using IC 50 (50% inhibitory concentration) (Figure 11 and Table S3, ESI †) and therapeutic index (TI = IC50 of normal cell to IC 50 of neoplastic cell ratio) (Figure 12 and Table S4, ESI †). It has been found that the cell proliferation showed a concentration and timedependent response to the test compounds.…”
Section: In Vitro Cytotoxic Activitymentioning
confidence: 99%
“…The test compounds were dissolved in a minimum amount of DMSO to assist solubility (should not exceed 0.1%–0.5% v/v to avoid its toxic effect on living cells. [ 94–96 ] The cell viability parentage against concentration through incubation periods 24 and 48 h are presented in Figure 10 (representative examples) and Figure S8, ESI.…”
Section: Biological Applicationsmentioning
confidence: 99%